2017
DOI: 10.1111/mam.12093
|View full text |Cite
|
Sign up to set email alerts
|

A biogeographical perspective on the variation in mouse lemur density throughout Madagascar

Abstract: Madagascar is home to the smallest primates in the world, the mouse lemurs (Microcebus species). Twenty‐four species of mouse lemur are currently recognised and are found in variable ecosystems, from dry forests and spiny deserts to humid forests. Due to their widespread distribution and the large number of sympatric species, mouse lemurs can be used as a model to understand the linkages among species richness, population density, and habitat. As all lemurs are threatened by habitat loss and fragmentation, thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 75 publications
1
27
0
Order By: Relevance
“…Home to ca. 110 currently recognized lemur taxa (Louis Jr. & Lei, 2016; Mittermeier et al, 2014; Setash, Zohdy, Gerber, & Karanewsky, 2017), Madagascar harbors the second-highest primate diversity of all countries and the highest proportion of primate endemism (Mittermeier et al, 2010). Mouse lemur habitats and population sizes are decreasing, while their level of threat is rising, mainly from deforestation, forest degradation, and poaching (IUCN, 2017; Schwitzer et al, 2013; Schwitzer, Mittermeier, et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Home to ca. 110 currently recognized lemur taxa (Louis Jr. & Lei, 2016; Mittermeier et al, 2014; Setash, Zohdy, Gerber, & Karanewsky, 2017), Madagascar harbors the second-highest primate diversity of all countries and the highest proportion of primate endemism (Mittermeier et al, 2010). Mouse lemur habitats and population sizes are decreasing, while their level of threat is rising, mainly from deforestation, forest degradation, and poaching (IUCN, 2017; Schwitzer et al, 2013; Schwitzer, Mittermeier, et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Dry and humid forest species typically have a different diet (Kappeler & Rasoloarison, 2003; Radespiel, 2007), and dry forests generally harbor higher population densities than humid forests (Randrianambinina et al, 2010; Setash et al, 2017). In addition, western dry and eastern humid regions harbor contrasting climatic conditions and climatic extremes that may have led to the development of independent unique resource use strategies (Génin, 2008, 2010; Kobbe & Dausmann, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Mouse lemurs comprise a radiation of morphologically cryptic primates distributed throughout Madagascar (Hotaling et al, 2016). Numerous studies have suggested that their rapid speciation dynamics may reflect climatic change through time in Madagascar (Andriatsitohaina et al, 2020;Setash et al, 2017) and that their unique life history characteristics make them an ideal genetic model organism (Ezran et al, 2017;Hozer et al, 2019). Thus, an accurate mutation rate estimate for these organisms can potentially yield valuable insight into both geological and biological phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…It is, therefore, important to investigate these responses (e.g. through population density estimates) across several species to identify macro-biogeographical and local ecological drivers of inter-and intraspecific variability in response to habitat (Setash et al 2017). Low-intensity selective logging or low-intensity bush-fallow agriculture can open up a habitat allowing increased levels of light penetration, which may have a positive effect on forest productivity and/or increased leaf quality (Ganzhorn 1995;Ganzhorn et al 1997;Oates 1996;Onderdonk and Chapman 2000;Skorupa 1986).…”
Section: Introductionmentioning
confidence: 99%